EFFECTS OF TRAMADOL ON THE MINIMUM ANESTHETIC CONCENTRATION OF ISOFLURANE IN WHITE-EYED PARAKEETS (PSITTACARA LEUCOPHTHALMUS) - Escobar, Andre [UNESP]; Rocha, Rozana Wendler da [UNESP]; Midon, Monica [UNESP]; Almeida, Ricardo Miyasaka de; Zangirolami Filho, Darcio [UNESP]; Werther, Karin [UNESP] (Amer Assoc Zoo Veterinarians, 2017)
The aim of this study was to determine the minimum anesthetic concentration (MAC) of isoflurane, and to investigate if tramadol changes the isoflurane MAC in white-eyed parakeets (Psittacara leucophthalmus). Ten adult birds weighing 157 +/- 9 g were anesthetized with isoflurane in oxygen under mechanical ventilation. Isoflurane concentration for the first bird was adjusted to 2.2%, and after 15 min an electrical stimulus was applied in the thigh area to observe the response (movement or nonmovement). Isoflurane concentration for the subsequent bird was increased by 10% if the previous bird moved, or decreased by 10% if the previous bird did not move. This procedure was performed serially until at least four sequential crossover events were detected. A crossover event was defined as a sequence of two birds with different responses (positive or negative) to the electrical stimulus. Isoflurane MAC was calculated as the mean isoflurane concentration value at the crossover events. After 1 wk, the same birds were reanesthetized with isoflurane and MAC was determined at 15 and 30 min after intramuscular administration of 10 mg/kg of tramadol using the same method. A paired t-test (P < 0.05%) was used to detect significant differences for MAC between treatments. Isoflurane MAC in this population of white-eyed parakeets was 2.47 +/- 0.09%. Isoflurane MAC values 15 and 30 min after tramadol administration were indistinguishable from each other (pooled value was 2.50 +/- 0.18%); they were also indistinguishable from isoflurane MAC without tramadol. The isoflurane MAC value in white-eyed parakeets is higher than reported for other bird species. Tramadol (10 mg/kg, i.m.) does not change isoflurane MAC in these birds.
Keywords: Anesthesia; birds; opioids; psittacidae; tramadol; white-eyed conures